О влиянии уровня внешнего магнитного поля и длины на магнитный момент цилиндрических сердечников - Чунихин, К.В. (Електротехніка і електромеханіка, 2018)
Рассмотрено магнитостатическое поле неоднородно намагниченного в однородном магнитном поле длинного цилиндрического сердечника электромагнита системы управления космическим аппаратом. Для расчета этого поля предложены преобразование интегрального уравнения относительно плотности фиктивных магнитных зарядов, а также итерационный алгоритм его численного решения. Сделан анализ влияния длины сердечника из пермаллоя 50Н во
всем диапазоне кривой намагничивания и уровня внешнего магнитного поля на осевую проекцию магнитного момента
сердечника, а также даны практические рекомендации относительно уровня внешнего поля, создаваемого катушкой
электромагнита, и увеличения магнитного момента в случаях длинных сердечников. Розглянуто магнітостатичне поле неоднорідно намагнеченого в однорідному магнітному полі довгого циліндричного
осердя електромагніту системи керування космічним апаратом. Для розрахунку цього поля запропоновані перетворення інтегрального рівняння відносно густини фіктивних магнітних зарядів, а також ітераційний алгоритм його
чисельного розв’язання. Зроблено аналіз впливу довжини осердя з пермалою 50Н у всьому діапазоні кривої намагнічування і рівня зовнішнього магнітного поля на осьову проекцію магнітного моменту осердя, а також надані практичні
рекомендації щодо рівня зовнішнього поля, створюваного котушкою електромагніту, і збільшення магнітного моменту в випадках довгих осердь. Purpose. Analysis of inhomogeneous magnetization of long
cylindrical permalloy 50N cores by a uniform constant magnetic
field and the influence of length and field level on their magnetic
moment. Methodology. The magnetostatic field of a nonuniformly magnetized in a uniform magnetic field long cylindrical core of an electromagnet of a spacecraft control system is
considered. To calculate this field, a transformation of the integral equation with respect to the density of fictitious magnetic
charges, as well as an iterative algorithm for its numerical solution, are proposed. Results. The convergence of the algorithm
and the fact that the magnetic moment of the core depends heavily on its length and the level of the external magnetic field is
shown. We have made an analysis of the influence of the length
of a permalloy 50N core in the entire range of the magnetization
curve and the level of a uniform external magnetic field on the
axial projection of the magnetic moment of the core. Originality.
The use of an almost equal distribution of the axial projection of
the resulting magnetic field in the cross sections of the greater
part of the cylindrical core and its division into cylindrical elements can significantly reduce the order of the system of algebraic equations approximating the integral equation for the
surface density of fictitious magnetic charges for its numerical
solution. Practical value. Recommendations regarding the level
of the external field created by the electromagnet coil, the increase of the magnetic moment in cases of long cores and the
choice of the number of cylindrical elements depending on the
length of the core are given.